1997
DOI: 10.1111/j.1471-6402.1997.tb00128.x
|View full text |Cite
|
Sign up to set email alerts
|

Bar Victimization of Women

Abstract: Little is known about the types and specific circumstances that surround the victimization of women who drink in the public context of bars. This study provides a preliminary description of the types of violence experienced by women bar drinkers and the roles of exposure and impairment as risk factors for encountering bar‐related aggression. Both quantitative and qualitative data were collected from 52 women bar drinkers through self‐administered questionnaires and focus‐group discussions about their lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
78
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 35 publications
6
78
1
Order By: Relevance
“…For example, bars and parties are locations which heavy drinking men and women frequent. Thus, these are situations in which perpetrators can easily find an intoxicated woman to target for a sexual assault (Parks & Miller, 1997). Several aspects of the situation are considered below and are summarized in Table 3 including the relationship between the perpetrator and the victim, the location of the assault, the perpetrators's misperception of the victim's sexual intentions, and alcohol's effects on how both the perpetrator and victim process information and react to each other.…”
Section: Situational Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, bars and parties are locations which heavy drinking men and women frequent. Thus, these are situations in which perpetrators can easily find an intoxicated woman to target for a sexual assault (Parks & Miller, 1997). Several aspects of the situation are considered below and are summarized in Table 3 including the relationship between the perpetrator and the victim, the location of the assault, the perpetrators's misperception of the victim's sexual intentions, and alcohol's effects on how both the perpetrator and victim process information and react to each other.…”
Section: Situational Factorsmentioning
confidence: 99%
“…The perpetrator and victim are less likely to be alone the entire time when either of them has been drinking alcohol (Abbey et al, 2001;Norris et al, 1998). In one study, one-third of the women who regularly drank in bars had been sexually assaulted at a bar or immediately after being at a bar (Parks & Miller, 1997).…”
Section: The Type Of Setting In Which the Sexual Assault Occurredmentioning
confidence: 99%
“…In an earlier survey with young (18-to 30-year-old) women bar drinkers, Parks (1999) found that nearly one third (30%) reported ever engaging in sexual intercourse with a casual sexual partner they met in a bar. In addition, women who drink in bars on a regular basis tend to be heavy episodic drinkers, consuming more than fi ve drinks, and report moderate to high intoxication on a usual night out (Parks and Miller, 1997;Parks and Zetes-Zanatta, 1999).…”
Section: High-risk Samplementioning
confidence: 99%
“…In one study, female heavy drinkers were found to be 2.8 times as likely to engage in unprotected sex and 2.1 times as likely to have multiple sex partners in the past year as female nondrinkers (Huang et al, 2010). More frequent drinking may result in women spending more time in places often associated with an increased likelihood of casual sex and sexual risk taking, including bars and parties, which may contribute to these associations (Bersamin et al, 2012;Parks and Miller, 1997). In addition, alcohol use and sexual risk behavior may co-occur as a result of common personality factors, such as sensation seeking and impulsivity (Caspi et al, 1995;Kalichman et al, 1996).…”
mentioning
confidence: 99%